Weed dynamic and control in peach palm (Bactris gasipaes k.) for palm hearts. - Bogantes-Arias, Antonio (2003)
The study was conducted atLos Diamantes Experiment Station, located in Guapiles,Costa Rica, to compare four sowing densities of thornlesspalms and two weed management strategies (chemical andphysical) on weed population dynamics of this crop, duringthe first year of growth. Weed cover and height, speciespresent and herbicide damage were among the variablesrecorded. Soil tillage prior to the crop establishmentpromoted weed germination from the seed bank. A total of31 weed species were recorded from a 3452 m2 experimentalarea during the first 14 months after sowing. An interactionbetween sowing distance and weed management strategieswas determined for gramineus and broadleaf species.Paspalum fasciculatum was the dominant species in plotsunder hand weeding while Ageratum conyzoides prevailed inglyphosate treated plots. Nine months after sowing, weedheight and cover along crop rows or between them weredifferent depending on the sowing density. In general,chemical weed control was efficient, although care should betaken during the first spraying when crop and weed height aresimilar, to avoid crop damage.